Development and Validation of Ribosomal RNA-Targeted Reverse Transcription Real-Time PCR Assays for the Sensitive and Rapid Diagnostics of High Consequence Pathogens - Merold, Veronika; Silberreis, Kim; Stoecker, Kilian (Frontiers in Microbiology, 2021)
Real-time PCR has become an essential tool in clinical microbiology and is been used for the acute diagnostics of many pathogens. Key performance indicators of real-time PCR assays are their specificity as well as their analytical and clinical sensitivity. One way to maximize the sensitivity of such diagnostic real-time PCRs is the use of genomic targets, which are present in several copies in the target cells. Here we use the naturally pre-amplified ribosomal RNA as target for specific and highly sensitive reverse-transcription real-time PCR detection of two high consequence pathogens, Yersinia pestis and Francisella tularensis. We determined their analytically sensitivity and illustrate that the newly designed assays are superior compared to other previous published real-time PCR assays. Furthermore, we used spiked clinical sample matrices to evaluate their clinical applicability. Finally, we demonstrate that these assays can be applied on heat-inactivated samples without the need of time-consuming nucleic acid extraction.